An annotated guideline to the use of a health economics analysis plan (heap) alongside randomised controlled trial - Dritsaki, M; Gray, A; Petrou, S; Dutton, S; Lamb, SE (BioMed Central, 2017)
Health economists working on clinical trial based economic evaluations are often asked at a preliminary stages of studies, and sometimes before data are available, to propose a plan for the collection and analysis of information on resource use, costs and quality of life. Questions that frequently arise when designing a Health Economics Analysis Plan (HEAP) for a clinical trial include what information should be included as standard within the HEAP, whether and how a proposed plan can be changed, how health economists and statisticians should split responsibility for data preparation and analyses, how missing data should be dealt with, and whether there are circumstances when a HEAP is not needed (for example in a feasibility study).